2019
DOI: 10.1177/1534735419889154
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Properties of Curcumin and Interactions With the Circadian Timing System

Abstract: The phytochemical curcumin is a major component of turmeric. It has recognized activity against cancer cells and affects several intracellular signaling pathways. Many molecules targeted by curcumin also regulate the circadian timing system that has effects on carcinogenesis, tumor growth, and metastasis. Although the circadian clock within cells may be suppressed in tumors, cancer cells are subjected to daily hormonal and neural activity that should be considered when timing optimal curcumin treatments. Rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 142 publications
0
4
0
Order By: Relevance
“…Additionally, it contributes to angiogenesis and cancer progression, associated with adverse clinical outcomes in GBM through activating TANK binding kinase 1 (TBK1) signaling pathway in ECs [ 549 ]. Inhibiting the CLOCK-BMAL1 complex counteracts its tumor-promoting effects on GBM and enhances BBB permeability [ 550 , 551 ], increasing the effective concentration of therapeutic drugs in the brain. This underscores the potential of CLOCK-BMAL1 as an important treatment target in GBM [ 552 , 553 ].…”
Section: Current Treatment Strategies and Progress Of Glioblastomamentioning
confidence: 99%
“…Additionally, it contributes to angiogenesis and cancer progression, associated with adverse clinical outcomes in GBM through activating TANK binding kinase 1 (TBK1) signaling pathway in ECs [ 549 ]. Inhibiting the CLOCK-BMAL1 complex counteracts its tumor-promoting effects on GBM and enhances BBB permeability [ 550 , 551 ], increasing the effective concentration of therapeutic drugs in the brain. This underscores the potential of CLOCK-BMAL1 as an important treatment target in GBM [ 552 , 553 ].…”
Section: Current Treatment Strategies and Progress Of Glioblastomamentioning
confidence: 99%
“… 104 Recently it has been reported that curcumin targets different molecules regulating the circadian timing system with anti-cancer activity such as PER2, BMAL1, and CLOCK. 105 Moreover, SR9009, which is considered a promising potential agent for GBM treatment, 26 , 92 can easily cross the BBB. 106 Interestingly, the circadian clock is involved in BBB permeability regulation in mammalian cells, 107 which highlights the crosstalk between circadian clock regulation and the efficiency of therapeutics delivery to the CNS during the treatment of GBM.…”
Section: Elements Of Clock As Therapeutic Targetsmentioning
confidence: 99%
“…The inhibitory effects of curcumin on breast cancer stem cells (BCSCs) have also been studied. Curcumin deregulated the process of EMT in breast cancer cells by reducing the proteins that play a key role in the formation of EMT such as Slug, AXL, twist1, N‐cadherin, β‐catenin, vimentin, and fibronectin (De, Beligala, Birkholz, & Geusz, 2019). The studies demonstrated the combination of curcumin with mitomycin C allows BCSCs to grow only the fourth generation.…”
Section: Curcumin Overcomes Drug Resistancementioning
confidence: 99%